Partnerships for prevention : the story of the Highfield Community Enrichment Project - Nelson, Geoffrey B. (Geoffrey Brian) (University of Toronto Press, 2005)
"This innovative study provides a wealth of knowledge that will be of interest and use to policy-makers, program planners, practitioners, and community residents who wish to create prevention programs."--Jacket